ANALISIS KINERJA SOSIAL DAN KINERJA KEUANGAN LEMBAGA KEUANGAN MIKRO (LKM) USAHA EKONOMI DESA-SIMPAN PINJAM (UED-SP) KECAMATAN PANGKALAN LESUNG KABUPATEN PELALAWAN. - Ika Retno Sari; Ahmad Rifai; Didi Muwardi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aims to analyze social performance and financial performance rural microfinance institutions (UED-SP) in Pangkalan Lesung Subdistric. Research was conducted at UED-SP Barokah in Sari Makmur village and UED-SP Sido Asri in Rawang Sari. Social performance analysis using MIX Market performance indicators, and financial performance analysis method using 17 ratio with Pearls. Analysis social performance and financial performance on average performed over the period 2011-2013. Results performance analysis showed that UED-SP in Pangkalan Lesung Subdistric has reached 10.77 percent - 19.57 percent of poor households, agricultural sector is the most reach on  productive activites. The volume loans increased at 70.58 percent on UED-SP Barokah, and 68.07 percent on UED-SP Sido Asri. Women borrowers increased at 87.19 percent on UED-SP Sido Asri and 98.66 percent on UED-SP Barokah. The results obtained analysis financial performance that rural microfinance in Pangkalan Lesung Subdistric does’t have a reserves for the loan risk on 1-12 months and over than 12 months. Effectiveness financial structure obtained very large ratio outstanding loans (94.21 percent), while loans and loan stock still small, and ratios of capital institutions ratios are very large. NPL ratio (4.35 percent) and unproductive assets ratio (00:05) is quite low. Ratio operating costs still high (11.96 percent), while ratio net income quite small (9.63 percent). Liquidity ratio good (4.94 percent). Signs look good capital growth with growth institutional capital sizeable (116.17 percent) and growth assets, loans and shares are above inflation. Keyword: UED-SP, Pangkalan Lesung, Sosial Ferformance, Financial Ferformance.